Male condition influences female post mating aggression and feeding in Drosophila. (4th May 2021) - Bath, Eleanor; Buzzoni, Daisy; Ralph, Toby; Wigby, Stuart; Sepil, Irem
Abstract: Mating changes female behaviour and physiology across a wide range of taxa, with important effects for male and female fitness. These changes are often induced by components of the male ejaculate, such as sperm and seminal fluid proteins. However, males can vary significantly in their ejaculates, due to factors such as age, mating history or nutritional status. This male variation may therefore lead to variation in the strength of responses males can stimulate in females, with alterations in fitness outcomes for both sexes. Using the fruit fly, Drosophila melanogaster, we tested whether three aspects of male condition shape an important, but understudied, post‐mating response—increased female–female aggression. We found that females mated to old males fought less than females mated to young males. This effect was exacerbated in mates of old, sexually active males, but there was no effect of male starvation status on mating‐induced female aggression. There was also a significant effect of age and mating history on female post‐mating feeding duration. Our results add to a growing body of literature that variation in male condition can shape sexual selection through post‐mating responses in females, including female–female interactions. Studying such variation may therefore be useful for understanding how the condition of one sex affects the behaviour of the other. A free plain language summary can be found within the Supporting Information of this article. Abstract : A free plain language summary can be found within the Supporting Information of this article.